The Science of Linguistics: Papers in Honour of Ștefan Oltean - FARKAS, Imola-Agnes; TODEA, Adriana (2020)
Professor Ștefan Oltean is celebrating his 70th birthday this July. This specialanniversary has occasioned this Festschrift, which we dedicate to him as we wereboth privileged to have him as our university professor, mentor and scientificadvisor of our doctoral dissertations, an experience that has had a long-lastinginfluence on our careers. The contributors to this volume – colleagues, friends,former and present PhD students – have gathered to celebrate this special occasion.